TMR for Peripheral Sensory Nerve Neuroma around the Wrist Utilizing the Distal Anterior Interosseous Nerve - Mohammed Muneer, MD (Plastic and Reconstructive Surgery, Global Open, 2024)
Summary:. Injury to the peripheral sensory nerves of the hand and wrist is common and can lead to debilitating neuromas and significantly impair patients’ quality of life. Target-muscle reinnervation (TMR) is a novel method for treating neuromas that can result in significant clinical improvement. However, TMR for the peripheral sensory nerves in the hand and wrist is restricted by the limited options for motor branches. The adaptability of the anterior interosseous nerve (AIN) as a target for TMR treating peripheral sensory neuroma has not been thoroughly investigated or implemented therapeutically. This study aimed to evaluate the use of AIN as a viable recipient of TMR for treating peripheral sensory neuromas around the wrist. In this retrospective study, eight patients were included over 18 months from June 2021 to January 2023 at Hamad Medical Corporation. The average follow-up time after TMR was 13 months. The peripheral sensory nerves involved were the radial sensory nerve in five cases, the palmar cutaneous branch of the median nerve in one case, and the median nerve in one case. The preoperative average VAS pain score was 7 of 10 compared with the postoperative pain score of 2 of 10. In conclusion, the AIN can be used as a first-choice motor target for all peripheral sensory neuromas around the wrist for the following reasons: first, it can be reached by the peripheral sensory nerves around the wrist; second, the pronator quadratus muscle is expandable; and third, the AIN can be taken with a long proximal tail for flexible coaptation with the peripheral sensory nerves.